Competitiveness of Indonesian Essential Oil Exports in the Chinese Market and Rival Countries - Dalimunthe, Nina Rahmida; Rosiana, Nia; Rifin, Amzul; Harmini, Harmini (Universitas Panji Sakti, 2025)
Indonesia is one of the world’s largest producers of essential oils; however, its export competitiveness in the Chinese market has fluctuated over time. This study aims to analyze the level and dynamics of Indonesia’s essential oil export competitiveness compared to other major exporting countries in the Chinese market. The research uses secondary time-series data from 2011 to 2023 obtained from Trade Map. Competitiveness is assessed using the Revealed Comparative Advantage (RCA) and Dynamic Revealed Comparative Advantage (DRCA) methods. The findings reveal that Indonesia generally demonstrates strong competitiveness, except in 2011 when it was weak and in 2022 when it was moderate. Based on DRCA, Indonesia was classified as a “rising star” in 2011–2013 and 2017–2019, a “falling star” in 2013–2015, a “lost opportunity” in 2019–2021, and experienced a decline to the “lagging retreat” position in 2015–2017 and 2021–2023. These fluctuations are influenced by unstable production, limited product innovation, and quality standards that do not fully align with market requirements. To strengthen its competitiveness, Indonesia must enhance product quality, adopt technological innovations, and foster collaboration among stakeholders.